2016
DOI: 10.1115/1.4034848
|View full text |Cite
|
Sign up to set email alerts
|

Loss Mechanisms of Interplatform Steps in a 1.5-Stage Axial Flow Turbine

Abstract: In this paper, the detailed steady and unsteady numerical investigations of a 1.5-stage axial flow turbine are conducted to determine the specific influence of interplatform steps in the first stator—as caused by deviations in manufacturing or assembly. A basic first stator design and a design consisting of a bow and endwall contours are compared. Apart from step height, the position and geometry of the interplatform border are varied for the basic design. To create the steps, every third stator vane was eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Many studies have applied SLT based on computational fluid dynamics (CFD) to the flow of turbomachinery. For reversible pump turbines, especially under the high-efficiency conditions of frequent operation, SLT can be used to track, visualize and eliminate FED (Jia and Liu, 2014;Zeinalpour and Mazaheri, 2015;Kluxen, et al, 2016). Among them, entropy production rate is one of the effective methods for FED quantitative analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have applied SLT based on computational fluid dynamics (CFD) to the flow of turbomachinery. For reversible pump turbines, especially under the high-efficiency conditions of frequent operation, SLT can be used to track, visualize and eliminate FED (Jia and Liu, 2014;Zeinalpour and Mazaheri, 2015;Kluxen, et al, 2016). Among them, entropy production rate is one of the effective methods for FED quantitative analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The region of high energy loss and the mechanism of loss formation are studied. Kluxen et al 21 carried out numerical analysis on the internal energy loss of axial-flow turbine. It is found that different local velocity will change the entropy production.…”
Section: Introductionmentioning
confidence: 99%
“…Kluxen et al. 28 studied the entropy production details in axial-flow turbine for loss reduction. Soltanmohamadi and Lakzian 29 conducted optimization design for turbine unit on the basis of entropy production visualization.…”
Section: Introductionmentioning
confidence: 99%